Structural elements made with highly flowable UHPFRC: Correlating computational fluid dynamics (CFD) predictions and non-destructive survey of fiber dispersion with failure modes. (15th February 2017) - Ferrara, Liberato; Cremonesi, Massimiliano; Faifer, Marco; Toscani, Sergio; Sorelli, Luca; Baril, Marc-Antoine; Réthoré, Julien; Baby, Florent; Toutlemonde, François; Bernardi, Sébastien
Highlights: Combines different cutting edge techniques for structural analysis of UHPFRC structures. Employs tailor made CFD tools for prediction of flow induced fiber orientation. Use ND magnetic method for fiber dispersion and orientation assessment. Compares CFD modelling and ND fiber monitoring results with structural failure patterns. Abstract: Structural design with highly flowable Fibre Reinforced Concrete has to duly take into account the preferential alignment of fibers, which can be governed through the rheological properties of the fluid mixture and the casting process and by the geometry of the structure. The possibility of predicting the fiber alignment, by tailoring the casting process, and of non-destructively monitoring it, can foster more efficient structural applications and design approaches. Focusing on UHPFRC slabs with pre-arranged casting defects, the flow-induced alignment of the fibers has been predicted by means of a suitable CFD modelling approach and hence monitored via a non-destructive method based on magnetic inductance properties of the fiber reinforced composite. The comparison between the assessed data on the fiber orientation and the crack patterns as visualized by image analysis supports the effectiveness of casting flow modelling and non-destructive fiber dispersion monitoring in supporting the structural design of elements made with highly flowable fiber reinforced cementitious composites.